The system of sports schools in respect with youth-training in Hungary - Balatoni, Ildikó; Kith, Nikoletta; Kosztin, Nikolett; Csernoch, László (Journal of Education, Health and Sport, 2016)
Abstract Purpose. The Hungarian government and the National Sport Strategy aim to preserve the results of our internationally recognized competitive sport by supporting youth-training. One of the components of youth-training is the system of sports schools. According to the Sport Law, the sports school is either an institution of public education, a commercial company, a sport club, or a foundation in which youth-training is done in an organized manner. Methods. We were interested to see if these sports schools would have an equal spatial distribution within the country, what is the age-distribution of their pupils, and, finally, do they have the necessary infrastructural background for their work. The research was conducted through a telephone survey in which 52 out of the 54 schools were included. Results. Half of the schools do not own all the necessary infrastructure that they would need to conduct proper training. This they try to solve by leasing them. Many of the schools (37%) specialize in three or four sport disciplines, and only a handsome (20%) coaches at least eight. While all together almost 36000 students are involved in the program, their number shows a large variation, from 50 to 1800, between the different schools. Conclusion. Sport infrastructure in Hungary in respect to youth-training shows a back-lag as compared to European standards. Nevertheless, due to the infrastructural developments and the subsidy of certain sports in the past few years, the opportunity to get engaged in sports and the available services have increased. Sports schools thus have a positive effect on youth-training and, through this, on physical education within the country.